PENGARUH PROMOSI, HARGA, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PERUMAHAN SUBSIDI VILLA SUTRA PADA PT. MITRA SABURAI PROPERTI - Hairudin Hairudin; Hasbullah Hasbullah (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
The purpose of this study was to examine the effect of promotion, price, and location on the decision to purchase subsidized housing at Villa Sutra at PT. Mitra Saburai Property. The data used in this study are primary data obtained from the results of distributing questionnaires. This research was conducted in the subsidized housing of Villa Sutra at PT. Mitra Saburai Property. The population in this study amounted to 35 consumers and the sample amounted to 35 consumers. The method used in this study is a quantitative method. The analytical tools used in this study used validity and reliability tests, classical assumption tests, multiple linear regression analysis tests, and hypothesis testing. Based on the results of the study concluded that the R Square obtained by 0.571 indicates that promotion, price, and location have the ability to explain purchasing decisions by 57,1%. The results of the F test concluded that simultaneously promotion, price, and location had a significant effect on the decision to purchase subsidized housing for Villa Silk at PT. Mitra Saburai Property. The results of the t test partially have a promotion that has a significant influence on purchasing decisions, partially price has a significant influence on purchasing decisions, partially location does not have a significant influence on purchasing decisions